Temperature Control for Induction Heating of Thin Strips. Issue 2 (2020) - Roetzer, F.; Aschauer, A.; Jadachowski, L.; Steinboeck, A.; Kugi, A.
Abstract: In this work, a model-based temperature controller for an induction heating system for moving thin metal strips is developed. The most significant disturbance of the system is an uncertain air gap geometry caused by flatness defects of the metal strip. A computationally expensive calculation of the electromagnetic field is avoided by using an equivalent circuit model and the energy balance. A thermal model of the moving strip is derived in the form of a convection-reaction equation and simplified to a linear time-invariant model. A 2-degrees-of-freedom controller is designed based on the simplified model and tested using a finite-element simulation model of the induction heating system. The simulations demonstrate that the proposed controller clearly outperforms standard feedback control strategies.